Phenolic cross-links: building and de-constructing the plant cell wall. Issue 7 (23rd January 2020) - Mnich, Ewelina; Bjarnholt, Nanna; Eudes, Aymerick; Harholt, Jesper; Holland, Claire; Jørgensen, Bodil; Larsen, Flemming Hofmann; Liu, Ming; Manat, Renil; Meyer, Anne S.; Mikkelsen, Jørn Dalgaard; Motawia, Mohammed Saddik; et al.
Abstract : Phenolic cross-links and inter-unit linkages result from the oxidative coupling of hydroxycinnamates leading to lignin assembly and cross-linking with cell wall polysaccharides and extensin proteins. Abstract : Covering: Up to 2019 Phenolic cross-links and phenolic inter-unit linkages result from the oxidative coupling of two hydroxycinnamates or two molecules of tyrosine. Free dimers of hydroxycinnamates, lignans, play important roles in plant defence. Cross-linking of bound phenolics in the plant cell wall affects cell expansion, wall strength, digestibility, degradability, and pathogen resistance. Cross-links mediated by phenolic substituents are particularly important as they confer strength to the wall via the formation of new covalent bonds, and by excluding water from it. Four biopolymer classes are known to be involved in the formation of phenolic cross-links: lignins, extensins, glucuronoarabinoxylans, and side-chains of rhamnogalacturonan-I. Lignins and extensins are ubiquitous in streptophytes whereas aromatic substituents on xylan and pectic side-chains are commonly assumed to be particular features of Poales sensu lato and core Caryophyllales, respectively. Cross-linking of phenolic moieties proceeds via radical formation, is catalyzed by peroxidases and laccases, and involves monolignols, tyrosine in extensins, and ferulate esters on xylan and pectin. Ferulate substituents, on xylan in particular, are thought to be nucleation points for lignin polymerization and are, therefore, of paramount importance to wall architecture in grasses and for the development of technology for wall disassembly, e.g. for the use of grass biomass for production of 2 nd generation biofuels. This review summarizes current knowledge on the intra- and extracellular acylation of polysaccharides, and inter- and intra-molecular cross-linking of different constituents. Enzyme mediated lignan in vitro synthesis for pharmaceutical uses are covered as are industrial exploitation of mutant and transgenic approaches to control cell wall cross-linking.